EFFECT OF BAR MODEL OF TEACHING MATHEMATICS ON THE ACHIEVEMENT OF IX STANDARD STUDENTS - Yanamashetti, Ramesh; Bamagond, Anil V. (International Journal of Psychosocial Rehabilitation, 2020)
Mathematics plays very important in student’s life. In any system of Education and also needed for day today life, Mathematics is basic and mandatory subject at Primary and Secondary level. The investigator is conducted an experimental Study on Bar Model of Mathematics. This is an innovative method of effect of Bar Model. The Pre-test study is conducted on Secondary School students. The sample by using experimental research consists of 70 students of IX std (35 Boys and 35 Girls). The instrument used in this research consists of questions of pre-test and post-test and a semi-structured interview. The statistical technique of the ANOVA and “t” tests was used. Data were analyzed by using SPSS 20.0 software and thematic analysis. The results showed that there is a significant difference in student’s mathematical problem-solving achievement. The analysis of semi-structured interview transcripts revealed that level of understanding and motivation influence students’ performance. Findings of this study showed that students perform better after the using of the Bar Model in Mathematical problem-solving. This study can provide an alternative or guidance for teachers to improve students’ mathematical problem-solving skills.